Glucose Regulatory Hormones in Camel, Cow, Goat, and Human Milk (P06-034-19). (13th June 2019) - Almohmadi, Wafa; Allen, Jonathan
Abstract: Objectives: Diabetes Mellitus is globally predicted to affect 592 million people by 2035 with the greatest rates of increase in low and middle income countries. Various plant and animal foods are being tested as alternatives to medication to control blood glucose. Regular consumption of milk from camels has had a positive anti-diabetic effect in both type 1 and type 2 diabetics. Epidemiological studies, research in diabetic rat and mouse model systems, and clinical studies in diabetic patients support the anti-diabetic effects of camel milk, but the mechanism of action is unclear. This study investigated hormones that impact glucose metabolism in humans from milks from different species and their stability with pasteurization. We tested hypotheses in the literature that camel milk antidiabetic properties are due to a high content of insulin or insulinotropic hormones. Methods: Five milk samples: Human, Bovine, Goat, and Camel from two different farms were analyzed with a multiplex panel for hormones that impact glucose metabolism in humans. Immunoreactivity to human Insulin, C-peptide, Glucagon, Ghrelin, Leptin, GIP, GLP-1, Resistin, Visfatin, and PAI-1 (total) were determined with a multiplex assay (Biorad Bioplex diabetes panel) using a Magpix analyzer. Results: Insulin immunoreactivity was present in both human and goat milk at approximately 200 pg/mL. Both camel samples were below the range of detection with this anti-human insulin antibody; but 5 pg/mL of insulin was detected in bovine milk. GIP was detected in all milks but was highest in human milk. Camel milk had higher immunoreactivity to resistin, visfatin, and ghrelin than goat or bovine milk. GLP-1 and leptin were only detected in human milk. Neither HTST nor Holder pasteurization significantly reduced the immunoreactivity of these hormones in milk. Conclusions: Although literature suggests camel milk is an effective medical food for diabetics, we did not find high insulin concentration in camel milk. The hypoglycemic effect of camel milk might be due to other components of camel milk. Assays using different antibodies or insulin receptors might show different results. The insulin concentration in goat milk suggests that this product should be tested as a medical food for glucose control. Funding Sources: NIFA; NCSU; Saudi Cultural Mission.